2013
DOI: 10.1080/17441692.2013.829862
|View full text |Cite
|
Sign up to set email alerts
|

A cost and technical efficiency analysis of two alternative models for implementing the basic package of health services in Afghanistan

Abstract: Since 2003, the Afghan Ministry of Public Health (MoPH) and international partners have directed a contracting-out model through which non-governmental organisations (NGOs) deliver the Basic Package of Health Services (BPHS) in 31 of the 34 Afghan provinces. The MoPH also managed health service delivery in three provinces under an alternative initiative entitled Strengthening Mechanisms (SM). In 2011, under the authority of the MoPH and Delegation of the European Union to Afghanistan, EPOS Health Management co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Each nongovernmental organization is expected to operate all primary care facilities in the province or cluster of districts within a province by providing a core set of services under the supervision of donor contract managers and proviancial health offices. Contracts vary slightly across the donor agencies, particularly with respect to inclusion of performance‐based elements, monitoring and evaluation mechanisms, and centralization or decentralization of essential drug and supply procurement …”
Section: Methodsmentioning
confidence: 99%
“…Each nongovernmental organization is expected to operate all primary care facilities in the province or cluster of districts within a province by providing a core set of services under the supervision of donor contract managers and proviancial health offices. Contracts vary slightly across the donor agencies, particularly with respect to inclusion of performance‐based elements, monitoring and evaluation mechanisms, and centralization or decentralization of essential drug and supply procurement …”
Section: Methodsmentioning
confidence: 99%
“…In the remaining three provinces, health services are provided directly by the Afghan government under the Strengthening Mechanism Project [ 4 ]. Previous research has revealed potential inefficiency in the NGO-run provinces (31) compared to the three provinces in which the Afghan government provides services directly [ 5 ]. The struggle to reduce inefficiencies in the health sector is not unique to Afghanistan.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid scale up of the BPHS has been attributed to the successful implementation of the NGO contracting mechanism [9]. The BPHS is delivered by NGOs in 31 of the 34 Afghan provinces and by the MOPH in three provinces using a contracting-in initiative entitled Strengthening Mechanisms (SM) [12]. …”
Section: Introductionmentioning
confidence: 99%